The Battle between Virus and Host: Modulation of Toll-Like Receptor Signaling Pathways by Virus Infection - Shin-ichi Yokota; Tamaki Okabayashi; Nobuhiro Fujii (Hindawi Limited, 2010)
In order to establish an infection, viruses need to either suppress or escape from host immune defense systems. Recent immunological research has focused on innate immunity as the first line of host defense, especially pattern recognition molecules such as Toll-like receptors (TLRs), RIG-I-like receptors (RLRs), and NOD-like receptors (NLRs). Various microbial components are recognized by their vague and common molecular shapes so-called, pathogen-associated molecular patterns (PAMPs). PAMPs induce inflammatory reactions mediated by the activation of the transcription factor, NF-𝜅B, and by interferons, which lead to an antiviral immune response. Viruses have the capacity to suppress or escape from this pattern recognition molecule-mediated antimicrobial response in various ways. In this paper, we review the various strategies used by viruses to modulate the pattern recognition molecule-mediated innate immune response.